(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The aim of the current research is to study the extent of female biology teachers awareness of scientific enlightenment by answering the following question, For the purpose of answering this question, the author prepared a scale for scientific enlightenment that includes seven areas, which are (Biological knowledge, the mutual relationship between biology, society and the environment, translation of terms, science processes, scientific directions, scientific inclinations and scientific assessment), The scale consists of 50 items that distributed equally over the seven areas of scientific enlightenment. The items for the first four areas were objective which means the answer was either true or false (takes 0-1), as for the last three areas the answer alternatives were three-fold (agree, hesitant, disagree) or (3-2-1). The research sample consisted of female biology teachers of Baghdad/ Al-Rusafa Third Education Directorate, amounting to 105 biology schools, who were chosen randomly from the middle, secondary, and preparatory schools about 150 schools. The results of the research concluded that biology teachers possess scientific awareness, depending on these results, the author developed recommendations and proposals to complement this research.